Foster a Culture of Literacy Through Increased Reading Interest in Village Communities - Muslimin Muslimin (Jurnal Cakrawala Pendidikan, 2018)
Abstract: This study aims to (1) describe in depth the causes of low reading interest of the community, especially the younger generation of school age, (2) to diagnose various causes of low reading interest, and (3) to find a model of reading activities that can encourage people to read so that the culture especially in the young generation of school age in the Village of Tabongo, district Tabongo, District East of Gorontalo. The methods used in this study qualitative method in the form of case studies by examining events or events related to reading interest and culture literacy. The technique of collecting data through observation, interviews, recording of data and images. Data analysis techniques, namely present, analyze, decompile, and exposes the data as is associated with the interests and culture of reading society. The research results showed that the reading interest in the community is still classified as low, because not yet available the means to read, educational level of the average graduate community primary school, dropping out of school, and lack of knowledge in literacy. To increase interest in reading in order to foster a culture of literacy needs to be carried out various strategies program that can reach out to all levels in society, namely the provision of means of library the village-based IT, student involvement KKN to teach how to read and write for two or three months, will need to work closely with nearby schools to grant access to the community dropped out from school in order to get a chance to learn.Keywords: interest in literacy, culture, reading, Gorontalo PENUMBUHAN BUDAYA LITERASI MELALUI PENINGKATAN MINAT BACA MASYARAKAT DESA Abstrak: Penelitian ini bertujuan untuk: (1) mendeskripsikan secara mendalam penyebab rendahnya minat baca masyarakat khususnya generasi muda usia sekolah; (2) mendiagnosis berbagai penyebab rendahnya minat membaca masyarakat; dan (3) menemukan model kegiatan membaca yang dapat mendorong masyarakat agar mau membaca sehingga terwujud budaya literasi khususnya pada generasi muda usia sekolah di Desa Tabongo Timur, Kecamatan Tabongo, Kabupaten Gorontalo. Pedekatan yang digunakan adalah pendekatan kualitatif dalam bentuk studi kasus dengan meneliti kejadian atau peristiwa terkait dengan minat baca dan budaya literasi. Teknik pengumpulan data melalui observasi, wawancara, dan rekaman data. Teknik analisis data dilakukan lewat penyajian, analisis, uraian, dan pemaparan data terkait dengan minat dan budaya membaca masyarakat. Hasil penelitian menunjukan bahwa minat membaca masyarakat masih tergolong rendah karena belum tersedia sarana untuk membaca, tingkat pendidikan masyarakat rata-rata tamatan sekolah dasar, putus sekolah, dan buta aksara. Untuk meningkatkan minat baca guna menumbuhkan budaya literasi perlu dilakukan berbagai strategi program yang dapat menjangkau seluruh lapisan masyarakat, seperti penyediaan sarana perpustakaan desa berbasis IT, pelibatan mahasiswa KKN untuk mengajar baca tulis selama dua sampai tiga bulan, perlu kerja sama dengan sekolah terdekat untuk memberikan akses kepada masyarakat putus sekolah guna mendapatkan kesempatan belajar.Kata Kunci: minat baca, budaya, literasi, Gorontalo